The interrelationship between confidence and correctness in a multiple-choice assessment: pointing out misconceptions and assuring valuable questions - Renata Grazziotin-Soares; Coca Blue; Rachel Feraro; Kristen Tochor; Thiago Machado Ardenghi; Donald Curtis; Diego Machado Ardenghi (Nature Publishing Group, 2021)
Abstract Introduction The aim of this study was to better understand the interfaces of being correct or incorrect and confident or unconfident; aiming to point out misconceptions and assure valuable questions. Methods This cross-sectional study was conducted using a convenience sample of second-year dental students (n = 29) attending a preclinical endodontics course. Students answered 20 multiple-choice questions ("basic" or "moderate" level) on endodontics, all of which were followed by one confidence question (scale). Our two research questions were: (1) How was the students' performance, considering correctness, misconceptions, and level of confidence? (2) Were the questions valuable, appropriate and friendly, and which ones led to misconceptions? Four situations arouse from the interrelationship between question correctness and confidence level: (1st) correct and confident, (2nd) correct and unconfident, (3rd) incorrect and confident (misconception) and (4th) incorrect and unconfident. Statistical analysis (α = 5%) considered the interaction between (a) students' performance with misconceptions and confidence; (b) question's difficulty with correctness and confidence; and (c) misconceptions with clinical and negative questions. Results Students had 92.5% of correctness and 84.6% of confidence level. Nine students were responsible for the 12 misconceptions. Students who had more misconceptions had lower correctness (P < 0.001). High achieving students had low confidence in their incorrect responses (P = 0.047). 'Moderate' questions had more incorrectness (P < 0.05) and less confidence (P = 0.02) than 'basic'. All questions were considered valuable [for example, the ones that presented images or required a mental picture of a clinical scenario, since they induced less misconception (P = 0.007)]. There was no difference in misconceptions between negative questions and other questions (P = 0.96). Conclusion Preclinical endodontic students were highly correct and very confident in their responses. Students who had more misconceptions had also the lowest performance in the assessment. Questions were valuable; but some will worth further improvement for the future. A multiple-choice assessment, when combined with confidence questions, provided helpful information regarding misconceptions and questions value.